Role of Bcl-2 in tumour cell survival and implications for pharmacotherapy - Tomek, M.; Akiyama, T.; Dass, Crispin (John Wiley & Sons Ltd., 2012)
Objectives: Bcl-2 is a protein that inhibits apoptosis, leading to cell survival. The Bcl-2 family has six different anti-apoptotic proteins, three pro-apoptotic proteins that are similar in structure, and other integrating proteins that function as promotors or inhibitors in the progression of apoptosis. In this discussion paper, we provide an overview of apoptosis, the role of Bcl-2 in normal cellular and molecular processes, and the role of Bcl-2 in tumour cell survival. It focuses primarily on anti-apoptotic Bcl-2, its activation in cancer, the manner in which it regulates the intrinsic and extrinsic mechanisms of apoptosis, and its broad molecular interactions with other critical proteins in the cell. Certain cancer treatments are reviewed and related directions for the future are presented.Key findings: Apoptosis is common to all organisms – for eukaryotes it is a normal process of development and regeneration. The rate at which apoptosis occurs is critical to the survival of the organism, as too much can lead to the onset of degenerative diseases such as dementia, and too little may lead to cancer. FKBP-38 is a binding protein that has been discovered to be upregulated in highly aggressive cancers and binds to Bcl-2 rather than the pro-apoptotics to induce a state of hyper-mitosis. A short binding protein (Nur-77) provides new insights into Bcl-2 ‘masking’. Nurr-77 binds to Bcl-2 and exposes the BH3 domain, transforming it from a cancer promoter to an unorthodox cancer inhibitor. This presents in itself an interesting and exciting opportunity – increasing the rate of apoptosis in neoplastic cells that are usually protected by Bcl-2 activity at the mitochondria.Summary: Development of drugs in the form of BH3-only and BH123 mimetic drugs provide a interesting avenue for cancer therapy for the future. Drugs that can either promote, or mimic anti-IAP activity such as Smac/Diablo would certainly be productive, thereby inducing apoptosis. Medicinal usage which can effectively suppress FKBP38 in Bcl-2-dependent cancers would provide further arsenal to combat apoptotic irregularities, particularly a treatment that is more dominant than kinetin riboside. WAVE-1 inhibitors may effectively suppress the phosphorylation of Bcl-2, thereby potentially reducing hyper-mitosis and increasing apoptosis. Recent findings shed molecular light on PDT, namely ER stress, and potential for anti-cancer therapy via either apoptosis or autophagy. Drugs that can effectively upregulate Nurr-77, thereby masking the anti-apoptotic properties of Bcl-2, would indeed be life-saving for cancer patients.